Pengaruh Brand Image, Online Customer Review Dan Persepsi Harga Terhadap Keputusan Pembelian The Originote Hyalucera Moisturizer Di Surabaya - Rinda Pramudya Pangesti; Endah Budiarti (Penerbit dan Percetakan CV.Picmotiv, 2025)
This research aims to analyze Brand Image, Online Customer Reviews and Price Perceptions on Purchasing Decisions for The Originote Hylucera Moisturizer in Surabaya. The population of this study were women who had purchased The Originote Hylucera Moisturizer with a sample of 97 respondents and determined using Non Probability Sampling. Primary data was obtained using a questionnaire while secondary data used literature study. Based on the SPSS Version 26 test results, it was found that the research instrument showed that all indicators were valid and all reliable. Based on the F test, all independent variables simultaneously influence purchasing decisions. Based on the results of the coefficient and t test, it shows that the brand image variable has a positive and significant effect on purchasing decisions, the online customer review variable has a positive and significant effect on purchasing decisions, and the price perception variable has a positive and significant effect on purchasing decisions.